The Influence of Social Media Marketing Activities on Brand Loyalty in Mobile Phone Products - Bambang Susanto; Endang Ruswanti (Green Publisher Indonesia, 2024)
Marketing activities through social media have become a common practice in the 21st-century business world. This has facilitated direct interaction between companies and consumers, engaging them in direct communication. This study aims to systematically and comprehensively examine the impact generated by social media marketing activities (SMMA) on the creation of brand awareness, brand image, and perceived quality. The research will measure the impact on brand equity resulting from the utilization of SMMA, specifically focusing on its influence on brand loyalty concerning mobile phone products within Indonesian society. The research will employ data collection through surveys and Structural Equation Modeling (SEM) methodology. The findings indicate that Social Media Marketing Activities (SMMA) have a positive and significant impact on brand awareness, brand image, and perceived quality. Furthermore, brand awareness, brand image, and perceived quality are proven to positively and significantly influence brand loyalty. Brand equity, represented by brand awareness, brand image, and perceived quality, has shown the ability to mediate the relationship between SMMA and brand loyalty. Further research could delve into the impact of SMMA on customer equity and expand the study by incorporating additional variables related to brand loyalty. Companies may benefit from investing in marketing efforts utilizing social media platforms as effective marketing tools.